2009
DOI: 10.1007/s12374-009-9049-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in SBPase Activity by Antisense RNA in Transgenic Rice Plants: Effect on Photosynthesis, Growth, and Biomass Allocation at Different Nitrogen Levels

Abstract: Rice cultivar zhonghua11 (Oryza sativa L. ssp. japonica) plants with decreased sedoheptulose-1, 7-bisphosphatase (SBPase) were obtained by transformation with the rice SBPase antisense gene under the control of the maize ubiquitin promoter. The transgenic and wild-type plants were grown at different nitrogen levels (0.1, 1, or 10 mM NH 4 NO 3 ). Growth rates of the seedlings were measured by the changes in dry weight, and the photosynthetic carbon reduction activities and the potential efficiency of photosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…The importance of SBPase in the control of the regenerative phase of the Calvin cycle has been shown by several studies; modelling and simulation studies have shown that SBPase exerts control over the rate of RuBP regeneration [ 23 , 24 ]. In studies that decreased SBPase levels in tobacco plants, reduced photosynthesis and growth were observed [ 25 27 ], with similar results found for rice [ 28 ]. Conversely, increases in the activity levels of SBPase led to increased photosynthesis and biomass in tobacco under controlled conditions [ 29 ] as well as in the field under elevated [CO 2 ] [ 30 ].…”
Section: Introductionsupporting
confidence: 65%
“…The importance of SBPase in the control of the regenerative phase of the Calvin cycle has been shown by several studies; modelling and simulation studies have shown that SBPase exerts control over the rate of RuBP regeneration [ 23 , 24 ]. In studies that decreased SBPase levels in tobacco plants, reduced photosynthesis and growth were observed [ 25 27 ], with similar results found for rice [ 28 ]. Conversely, increases in the activity levels of SBPase led to increased photosynthesis and biomass in tobacco under controlled conditions [ 29 ] as well as in the field under elevated [CO 2 ] [ 30 ].…”
Section: Introductionsupporting
confidence: 65%
“…The enzyme SBPase participates in the final regenerative phase of the Calvin cycle by catalyzing the dephosphorylation of sedoheptulose 1,7-bisphosphate to produce the CO 2 acceptor molecule RubP for the continued functions (Raines et al, 1999 ). This enzyme is unique to the Calvin cycle, and its activity affects photosynthesis, growth, and biomass allocation (Feng et al, 2009 ). It has been reported that decreased activity of SBPase can result in a significant reduction in the rate of light- and CO 2 -saturated photosynthesis (Harrison et al, 1998 ), and over-expression of SBPase can enhance carbon assimilation and crop yields (Rosenthal et al, 2011 ; Jessica et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes catalyze the dephosphorylation of fructose-1,6-bisphosphate and sedoheptulose-1,7-bisphosphate in the so-called regeneration phase of the Calvin Benson cycle (Cotton et al, 2015;Feng et al, 2014;Tamoi et al, 1996). RuBisCO and SBPase, along with aldolase, have been identified as ratelimiting enzymes in the Calvin cycle (Ding et al, 2016;Feng et al, 2009;Harrison et al, 1997Harrison et al, , 2001; Hudson et al, 1992;Haake et al, 1998Haake et al, , 1999Izumi et al, 2012;Lauerer et al;Lawson et al, 2006;Olçer et al, 2001;Raines, 2003;Zhu et al, 2007). Additionally, cyanobacteria possess a carbon concentrating mechanism (CCM) that can concentrate inorganic carbons in the cytosol through energy consuming processes coupled to Na + gradients, ATP hydrolysis, and/or oxidation of NAD(P)H (Rae et al, 2013).…”
Section: Introductionmentioning
confidence: 99%